Toward an Ethical Framework for the Text Mining of Social Media for Health Research: A Systematic Review - Ford, Elizabeth; Shepherd, Scarlett; Jones, Kerina; Hassan, Lamiece (Frontiers in Digital Health, 2021)
Background: Text mining techniques are advancing all the time and vast corpora of social media text can be analysed for users’ views and experiences related to their health. There is great promise for new insights on health issues such as drug side effects and spread of disease, as well as patient experiences of health conditions and health care. However, this emerging field lacks ethical consensus and guidance. We aimed to bring together a comprehensive body of opinion, views and recommendations in this area so that academic researchers new to the field can understand relevant ethical issues. Methods: After registration of a protocol in PROSPERO, three parallel systematic searches were conducted, to identify academic articles comprising commentaries, opinion and recommendations on ethical practice in social media text mining for health research and grey literature guidelines and recommendations. These were integrated with social media users’ views from qualitative studies. Papers and reports that met the inclusion criteria were analysed thematically to identify key themes and an overarching set of themes was deduced. Results: A total of 47 reports and articles were reviewed and eight themes were identified. Commentators suggested that publicly posted social media data could be used without consent and formal research ethics approval, provided that the anonymity of users is ensured, although we note privacy settings are difficult for users to navigate on some sites. Even without the need for formal approvals we note ethical issues: to actively identify and minimise possible harms, to conduct research for public benefit rather than private gain, to ensure transparency and quality of data access and analysis methods, and to abide by the law and terms and conditions of social media sites. Conclusion: Although social media text-mining can often legally and reasonably proceed without formal ethics approvals, we recommend improving ethical standards in health-related research by: increasing transparency of the purpose of research, data access and analysis methods; consultation with social media users and target groups to identify and mitigate against potential harms that could arise; and ensuring the anonymity of social media users.